Impact of Covid-19 on Foodservice Operations Within Urban Kansas Childcare Centers - Jindrich, Caitlin; Daniels, Elizabeth; Hanson, Jennifer Ann (My University, 2022)
Methods: Three COVID-19-related questions were added to an online survey of Child and Adult Care Food Program (CACFP) participating childcare centers located throughout Kansas. Responses were collected from July through August, 2020. Descriptive statistics and thematic analysis of open-ended responses were used to identify common concerns. Results: Seventy-nine of the 138 childcare centers invited to complete the COVID-19-related questions responded (57.2% participation rate). The majority (n = 56, 70.1%) reported decreased enrollment, whereas a small number (n = 9, 11.4%) reported an increase. Approximately two-thirds of the centers (n = 49, 62.0%) reported foodservice operation modifications owing to COVID-19-related challenges. Three overarching themes were discovered within the centers’ responses: a) procurement challenges including decreased availability and increased cost of foods, b) changes in meal service including shifting to disposable tableware and ceasing family-style meal service, and c) menu and production changes in response to enrollment changes and product availability issues. Application to Child Nutrition Professionals: Future consideration for CACFP participants include shifting to more shelf-stable foods when faced with food availability issues and utilizing more cost-effective food purchasing options, which might be attained through group purchasing organizations. Well-developed emergency plans such as emergency menus should include plans for procurement challenges. Resources and training to increase understanding and knowledge of CACFP meal pattern guidelines may make menu changes based on availability easier or less challenging. Best practice guidelines, such as family-style meals, may have to take health and safety measures into consideration. As centers continue to experience COVID-19-related issues and plan for a “return to normal”, child nutrition professionals can fulfill an important role in helping centers adapt their foodservice operations to meet the challenge.
Keywords: Early Care and Education; Child Nutrition; COVID-19; Foodservice; Food Procurement